Facilitating Listening and Speaking at Primary Level Using Intelligent Personal Assistant (IPA) - Verma, Abhishek; Sanjay Arora (THE PRIMARY TEACHER, 2022)
Intelligent Personal Assistant (IPA) enables Natural Language Interface between human and machine through translation of human intentions into commands by recognising users’ speech and gestures. The study focuses on facilitating listening and speaking of lowcompetence learners at the primary level through IPA. Students at the primary level lack the opportunity to communicate in the target language, which makes them hesitant as well as anxious while using L2 in public. The proposed paper aims to understand the limitations and pedagogical usage of smart speakers such as Amazon Echo and its associated voice-controlled Intelligent Personal Assistant (IPA) Alexa for primary-level students. The researchers believe that these devices help the learners in practicing, speaking and listening in a stress-free environment and also promote learner autonomy (out-of-class learning). They intend to develop a few exercises that users can undertake to make a meaningful ‘human-computer’ interaction with IPA devices